(untitled) (CIPEEX, 2025)
Introduction: Lower limb trauma significantly affects functionality, autonomy, and quality of life, often leading to both short- and long-term disability. Uncontrolled postoperative pain is a major factor in the development of chronic pain, and kinesiophobia can exacerbate this process. High kinesiophobia levels may result in avoidance behaviors and reduced physical activity, hindering recovery and creating a cycle of increasing pain and disability. Objective: To evaluate the association between pain levels and kinesiophobia in immediate postoperative patients with lower limb trauma. Methodology: This cross-sectional study was conducted at an orthopedic referral hospital in north-central Goiás, with ethical approval (protocol no. 6970562). The study involved 92 volunteers (68.5% male; mean age: 39.18 ± 11.28 years) in the postoperative period following lower limb trauma. The Tampa Scale of Kinesiophobia (TSK) and Visual Analog Scale (VAS) were used to measure kinesiophobia and pain levels, respectively. Statistical analyses were performed using the Chi-square test. Results: • 71.7% of participants exhibited moderate levels of kinesiophobia, and 81.5% reported kinesiophobia to some degree. • Moderate pain levels were predominant in both genders, with 72.4% of women and 71.4% of men reporting this level. • No significant association was found between kinesiophobia and gender (p=0.711), pain levels and kinesiophobia (p=0.937), or pain levels and gender (p=0.785). Conclusion: There is a high prevalence of moderate kinesiophobia and pain among immediate postoperative patients with lower limb trauma. While no significant associations were found between the variables, the findings underscore the importance of addressing psychological factors like kinesiophobia in rehabilitation programs. Further research is needed to understand these relationships and develop strategies to improve recovery outcomes.